2008
DOI: 10.1007/s10616-008-9164-x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome number variation in three mouse embryonic stem cell lines during culture

Abstract: Although mouse embryonic stem cell lines (mESCs) have been established since 1981, systematic studies about chromosomal changes during culture are lacking. In this study, we report the results of a cytogenetic analysis performed on three mESC lines (named UPV02, UPV06 and UPV08) cultured for a period of 3 months. At time intervals, the variation of the chromosome number together with the expression of markers of the undifferentiated status, i.e., OCT-4, SSEA-1, FOM-1 and alkaline phosphatase activity, were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
2
12
1
Order By: Relevance
“…At passage 8, karyotype analysis showed that all lines from preblastocysts had over 70% euploid chromosome count. This percentage is in normal range of reported mouse ES cell lines (Rebuzzini et al, 2008a(Rebuzzini et al, , 2008b. Teratoma study is very important assay to demonstrate pluripotent cell lines' differentiation and pluripotency.…”
Section: Characterization Of Es Cells From Preblastocystsupporting
confidence: 54%
“…At passage 8, karyotype analysis showed that all lines from preblastocysts had over 70% euploid chromosome count. This percentage is in normal range of reported mouse ES cell lines (Rebuzzini et al, 2008a(Rebuzzini et al, , 2008b. Teratoma study is very important assay to demonstrate pluripotent cell lines' differentiation and pluripotency.…”
Section: Characterization Of Es Cells From Preblastocystsupporting
confidence: 54%
“…As mentioned previously, we have also observed a high level of chromosome 11 and 14 trisomies. Interestingly, we observed chromosome 1 trisomy in many cells of the ES cell lines, and its high frequency has not been previously reported (Liu et al 1997;Sugawara et al 2006;Rebuzzini et al 2008b).…”
Section: Discussioncontrasting
confidence: 44%
“…In other three mESC lines, named UPV02, UPV06 and UPV08, a progressive loss of euploid metaphases during culture has been observed and chromosome abnormalities, in particular metacentric chromosomes, accumulated at the latest passages analysed (passage 31, 29 and 22 for UPV02, UPV06 and UPV08, respectively). We observed that in coincidence with, or few passages after, the drop of euploidy, the alkaline phosphatase activity, one important ESC marker, was partially or totally lost (Rebuzzini et al, 2008b). Rat The rat ESCs (rESCs) are an important resource for the study of disease models, however, despite several temptatives (Brenin et al, 1997;Vassilieva et al, 2000) they have been derived only very recently (Buehr et al, 2008;Ueda et al, 2008;Zhao et al, 2010).…”
Section: Non-human Primatesmentioning
confidence: 93%
“…Mouse Unexpectedly, an accurate literature search showed that only a few papers described the genomic variation of mESCs during a long period of culture. In many mESC lines, no recurrent chromosome abnormalities, but rather random alterations have been described by some laboratories (Longo et al, 1997;Guo et al, 2005;Sugawara et al 2006;Rebuzzini et al, 2008a;Rebuzzini et al, 2008b). The most complete analysis that has been made on mESCs was performed by Sugawara and colleagues (Sugawara et al, 2006).…”
Section: Non-human Primatesmentioning
confidence: 99%
See 1 more Smart Citation